Jürgen Habermas and Bush’s Neoconservatives: Too Close for Comfort? - Vivienne Matthies-Boon (Studies in Social Justice, 2011)
In his recent political writings, Habermas has opposed his cosmopolitan project to that of the Bushite neoconservatives.  However, this article argues that in some respects Habermas's works come closer to the neoconservative agenda than he realizes and that this poses a potential danger of its being appropriated by precisely the camp he opposes.  These problems particularly come to the fore in his analysis of Islamic fundamentalism, democracy and the Middle East, but also in his recommendations concerning UN-based internationalism and his appeals to Woodrow Wilson.  By tracking these problematic areas in Habermas's work, this article argues that Habermas needs to engage in a more carefully articulated, concrete and empirical analysis if he is to avoid these problems.